(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The importance of understanding how consumers gather and evaluate information about the new products is essential for providers. This paper considers the student population as consumers and attempt to determine where students as consumers learn information about new products and their attitudes toward different sources of information. Research was conducted at the Polytechnic in Sibenik and comprised students of all majors and years of study. Results indicated that students as consumers utilize a wide variety of information sources to learn about new products. Thus gender, as a major social category, age and other determinants of consumer behaviour were also considered. It concludes with some important marketing implications. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.